1982
DOI: 10.1111/j.1477-9552.1982.tb00710.x
|View full text |Cite
|
Sign up to set email alerts
|

Perverse Substitution Relationships in Demand Studies: The Example of Butter and Margarine

Abstract: Econometric analyses of demand for butter in a number of countries have produced results which appeared to conflict with expectations. Specifically the sign of the co-efficient for margarine price was negative rather than the positive sign expected with a presumed substitute product. Gollnick (1954), who was the first econometrician to meet this problem, advanced the hypothesis of a constant fat budget to explain the paradox. Among other works which reported similar paradoxical results were Hesse (1967), Wiere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The Rotterdam model suggests that demand for cheese and table spreads is substantially more own-price elastic than previous studies indicated (e.g., Boehm, 1975;Haidacher, Blaylock, & Myers, 1988;Heien & Wessells, 1988;Huang, 1993;Pitts & Herlihy, 1982). Weekly data often appear to produce more elastic estimates than do monthly, quarterly, or annual disappearance data.…”
Section: Resultsmentioning
confidence: 83%
“…The Rotterdam model suggests that demand for cheese and table spreads is substantially more own-price elastic than previous studies indicated (e.g., Boehm, 1975;Haidacher, Blaylock, & Myers, 1988;Heien & Wessells, 1988;Huang, 1993;Pitts & Herlihy, 1982). Weekly data often appear to produce more elastic estimates than do monthly, quarterly, or annual disappearance data.…”
Section: Resultsmentioning
confidence: 83%
“…Negative cross-import price elasticities, on the other hand, indicate a complemen-tary relation between the products. A complementary relationship can occur for staple foods (such as rice) with a relatively fixed expenditure outlay, and own-price elasticities less than one (Pitts and Herlihy, 1982). As can be seen in Table 3, this relationship occurs in a number of cases.…”
Section: Import Demand Price and Expenditure Elasticitiesmentioning
confidence: 99%
“…Negative cross-irnport priee elasticities, on the other hand, indicate a cornplernen-tary relation between the products. A complementary relationship can occur for staple foods (such as riec) with a relatively fixed expenditure outlay, and own-price elasticities less than one (Pitts and Herlihy, 1982). As can be seen in Table 3, this relationship occurs in a number of cases.…”
Section: Import Demand Priee and Expenditure Elasticiticsmentioning
confidence: 99%